Checklist on Integrating Gender Considerations in Climate Services and Safety Nets - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
This checklist is based on research and synthesis of CCAFS experience in CIS, and a compilation of lessons learned for good practice in gender integration.